CASE STUDY. IMPACT OF SOCIAL MEDIA ON MENTAL HEALTH OF STUDENTS - Dilnoza Kamoliddinova; Fozilbek Orzibekov (TADQIQOTLAR, 2025)
Abstract Considering the significant and constant use of social networks in the world, mostly by young women, we reflect in this article on the relationship between digital communication technologies and their influence on student perspectives, as well as their repercussions on mental health and academic performance. The aim was to describe the reasons that lead university students to access social networks; outline the harms of using these platforms, if any, in their life experiences; investigate the influence of social networks on their productivity, thus seeking to understand the use of social networks and their interface with the mental health of these students. This is a descriptive-exploratory study, with a qualitative approach, carried out with 16 students of Kimyo International University in Tashkent (Samarkand Branch). A semi- structured interview was used, and thematic content analysis was followed for its interpretation. Information collection took place in November 2019 and all ethical aspects were respected. The results indicated different perceptions regarding the use of social networks that produce impacts on the mental health, personal and academic lives of the university students interviewed. Furthermore, it was found that social networks contribute to the dynamism and autonomy of the learning process, while the excessive use of these platforms can have a detrimental effect on students’ mental health and academic performance.